(untitled) (Iter, 2022)
I n the light ofa re-reading o f Enrico CastellVs work, the author gives herey along with a profile o f the philosopher, a moved memory ofhe who was his masterand particular features of his peculiar way of thinking. What stands out in a special way is the place common sense and lived experience occupy over all kinds of traditional intellectualism; and it defines his philosophy as a “theological existencialism ”.